Pengaruh perpustakaan sekolah terhadap minat baca siswa sekolah dasar di era digital 4.0 - Faiseh, Aulitul (Maliki Interdisciplinary Journal, 2024)
English abstract. Students' high interest in reading is important in improving the quality of education in Indonesia. The high interest in reading among students is determined by the use of the library as a learning resource. The library is a supporting tool for students in increasing interest in reading, especially in the midst of the digital era as it is today. The library itself is a benchmark for students how capable students are in understanding a reading. Therefore schools must have their own library to make it easier for students to increase interest in reading and add insight in knowing very important information.